Capillaroscopy in autoimmune rheumatic diseases - Cutolo, Maurizio (Henry Stewart Talks, 2007)
Materials and methods for the correct employment of the video capillaroscopy, The Raynaud's phenomenon and the role of capillaroscopy, The scleroderma pattern today, Scleroderma pattern and pathophysiological significance, Frequent patterns in dermatomyositis, systemic lupus erythematosus and antiphospholipid syndromes, Correlations between the capillaroscopic patterns and clinical and laboratory findings